Unobtrusive ballistocardiography using an electromechanical film to obtain physiological signals from children with autism spectrum disorder - Rubenthaler, Steve (Kansas State University, 2014)
Polysomnography is a method to obtain physiological signals from individuals with potential sleep disorders. Such physiological data, when acquired from children with autism spectrum disorders, could allow caregivers and child psychologists to identify sleep disorders and other indicators of nighttime well-being that affect their quality of life and ability to learn. Unfortunately, traditional polysomnography is not well suited for children with autism spectrum disorder because they commonly have an aversion to unfamiliar objects – in this case, the numerous wires and electrodes required to perform a full polysomnograph. Therefore, an innovative, unobtrusive method for gathering relevant physiological data must be designed. This report discusses several methods for obtaining a ballistocardiogram (BCG), which is a representation of the ballistic forces created by the heart during the cardiac cycle. A ballistocardiograph design is implemented using an electromechanical film placed under the center of a bed sheet. While an individual sleeps on the bed, the circuitry attached to the film extract and amplify the BCG data, which are then streamed to a computer through a LabVIEW interface and stored in a text file. These data are analyzed with a MATLAB algorithm which uses autocorrelation and linear predictive coding in the time domain to sharpen the signal. Frequency-domain peaks are then extracted to determine average heart rate every ten seconds. Initial tests involved four participants (student members of the research team) who laid in four positions: on their back, stomach, right side, and left side, yielding 16 unique data sets. Each participant laid in at least one position that allowed for accurate tracking of heart rate, with seven of the 16 signals demonstrating heart rates with less than 2% error when compared to heart rates acquired with a commercial pulse oximeter. The stomach position appeared to offer the lowest total error, while lying on the right side offered the highest total error. Overall, heart rates acquired from this initial set of participants exhibited an average error of approximately 2.5% for all four positions.
Keywords: Ballistocardiography; Autism; Unobtrusive; Electromechanical film; Biomedical Engineering (0541); Computer Engineering (0464); Electrical Engineering (0544); Engineering (0537)